The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1152/ajpgi.00020.2018
|View full text |Cite
|
Sign up to set email alerts
|

A rotating light cycle promotes weight gain and hepatic lipid storage in mice

Abstract: Processes involved in regulation of energy balance and intermediary metabolism are aligned to the light-dark cycle. Shift-work and high fat diet (HFD)-induced obesity disrupt circadian rhythmicity and are associated with increased risk of non-alcoholic fatty liver disease (NAFLD). This study aimed to determine the effect of simulating shift work on hepatic lipid accumulation in lean and HFD-mice. C57BL/6 mice fed a standard laboratory diet (SLD) or HFD for 4wks were further allocated to a normal light (NL)-cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 58 publications
2
31
0
Order By: Relevance
“…Desynchronization of circadian clocks by altering the timing of food intake can lead to uncoupling of peripheral clocks with the central clock which subsequently leads to the development of metabolic disorders . For example, in the mice from the current study fatty liver was observed in the SLD‐RL mice to the same level as that observed in the HFD‐mice . The adverse effects of desynchronization of circadian clocks are not limited to metabolic syndrome, with disruption of the circadian system an important contributor to a number of pathological diseases including various gastrointestinal disorders such as gastrointestinal motility disorders .…”
Section: Discussionmentioning
confidence: 64%
See 4 more Smart Citations
“…Desynchronization of circadian clocks by altering the timing of food intake can lead to uncoupling of peripheral clocks with the central clock which subsequently leads to the development of metabolic disorders . For example, in the mice from the current study fatty liver was observed in the SLD‐RL mice to the same level as that observed in the HFD‐mice . The adverse effects of desynchronization of circadian clocks are not limited to metabolic syndrome, with disruption of the circadian system an important contributor to a number of pathological diseases including various gastrointestinal disorders such as gastrointestinal motility disorders .…”
Section: Discussionmentioning
confidence: 64%
“…Weight gain and gonadal fat pad mass have been reported previously . Briefly, there was no difference in the body weight of the mice randomly allocated to the 4 different groups (Table ).…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations